Efforts to embedding character education in class X history learning in the independent curriculum at SMA Negeri 4 Pekanbaru: Upaya Penanaman Pendidikan Karakter Dalam Pembelajaran Sejarah Kelas X Pada Kurikulum Merdeka di SMA Negeri 4 Pekanbaru - Riski Anggola; Isjoni; Yanuar Al Fiqri (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The purpose of this research was to identify and obtain information about the school's efforts to embedding character education in the independent curriculum, especially in history learning. The method used in this research is a descriptive qualitative method, which describing the situation and data obtained during the author's observations and interviews by asking questions so that it becomes information that is useful and easy for the reader to understand. This research explains and provides an overview of the efforts made by the school in embedding character education in class X history learning in the independent curriculum at SMA Negeri 4 Pekanbaru. The research results indicate that efforts to embedding character education in class X history learning in the independent curriculum at SMA Negeri 4 Pekanbaru are ongoing and implemented optimally in accordance with the school's policies and capabilities. In implementing character education in schools, it does not only rely on the learning process in the classroom, but is also carried out by providing positive activity habits for students and P5, although in its implementation there are still many shortcomings and obstacles.